2009
DOI: 10.1038/bmt.2009.92
|View full text |Cite
|
Sign up to set email alerts
|

High burden of late effects after haematopoietic stem cell transplantation in childhood: a single-centre study

Abstract: The aim of our study was to assess the cumulative incidence and severity ('burden') of late effects in a single-centre cohort of childhood haematopoietic stem cell transplantation (HSCT) survivors, at least 2 years after transplantation. The presence and severity of late effects in each survivor was documented according to the Common Terminology Criteria for Adverse Events (version 3.0). The burden of late effects was graded from mild to disabling/life-threatening. Risk factors for a high burden of late effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 38 publications
8
69
1
1
Order By: Relevance
“…This determining role of preparative regimens is in accordance with previous studies that identified TBI as a risk factor for more frequent and more severe late effects in pediatric HSCT recipients. 2,16,17 This was not observed in a BMTSS study describing self-reported complications in mostly adult patients. 18 Child-specific adverse events like growth retardation might account for this difference.…”
Section: Discussionmentioning
confidence: 67%
“…This determining role of preparative regimens is in accordance with previous studies that identified TBI as a risk factor for more frequent and more severe late effects in pediatric HSCT recipients. 2,16,17 This was not observed in a BMTSS study describing self-reported complications in mostly adult patients. 18 Child-specific adverse events like growth retardation might account for this difference.…”
Section: Discussionmentioning
confidence: 67%
“…[11][12][13][14] In the Bone Marrow Transplant Survivor Study (BMTSS), Armenian et al found a 79.0% prevalence of grade 1-4 and 25.5% of grade 3-4 self-reported chronic conditions among 145 childhood HSCT survivors (mean age, 24.0 years) surveyed 11 years post-HSCT. 11 A Dutch study that used clinical data to ascertain chronic conditions among 162 survivors of childhood HSCT (median age, 13.5 years) with 7 years of follow-up reported a lower prevalence of any grade or grade 3-4 chronic conditions (93.2% and 25%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Singlefraction TBI (sTBI) 10-12 Gy with CY (120 mg/kg) was used at the University Hospital in Huddinge during 1978-1995 and at the Helsinki University Hospital during [1978][1979][1980][1981][1982][1983]. Fractionated TBI (fTBI) was introduced in Helsinki in 1984 (10)(11)(12) Gy in 5-6 fractions) and in Huddinge in 1993 (12 Gy in 4 fractions). Patients with SAA have received CY (200 mg/kg) with or without TLI 6 Gy or fTBI 10 Gy.…”
Section: Treatment Characteristicsmentioning
confidence: 99%
“…Most studies have included patients with comparatively short follow-up times, often o 4 years, 6,9 or been limited by lack of follow-up data into late puberty or adulthood. 10 As long-term survival is an expected outcome for many pediatric patients undergoing HSCT, the treatment-related late toxicities are becoming increasingly important. In a retrospective cohort study, we aimed to evaluate the frequency, spectrum and risk factors of late effects in a cohort of pediatric allogeneic HSCT (allo-HSCT) survivors with longitudinal follow-up data into late puberty or adulthood.…”
Section: Introductionmentioning
confidence: 99%